Upper GI Tract Lesions in Familial Adenomatous Polyposis (FAP): Enrichment of Pyloric Gland Adenomas and Other Gastric and Duodenal Neoplasms - Wood, Laura D. (2014)
Patients with familial adenomatous polyposis (FAP), an autosomal dominant cancer predisposition syndrome caused by mutations in the APC gene, develop neoplasms in both the upper and lower gastrointestinal (GI) tract. To clarify the upper GI tract lesions in FAP patients in a tertiary care setting, we reviewed specimens from 321 endoscopies in 66 patients with FAP. Tubular adenomas in the small bowel were the most common neoplasms (present in 89% of patients), although only 1 patient developed invasive carcinoma of the small bowel. Several types of gastric neoplasms were identified—65% of patients had at least 1 fundic gland polyp, and 23% of patients had at least 1 gastric foveolar–type gastric adenoma. Pyloric gland adenomas were also enriched, occurring in 6% of patients—this is a novel finding in FAP patients. Despite the high frequency of gastric neoplasms, only 1 patient developed carcinoma in the stomach. The very low frequency of carcinoma in these patients suggests that current screening procedures prevent the vast majority of upper GI tract carcinomas in patients with FAP, at least in the tertiary care setting.